The Economics and Law of Sovereign Debt and Default - Panizza, Ugo; Sturzenegger, Federico; Zettelmeyer, Jeromin (Journal of Economic Literature, 2009)
This paper surveys the recent literature on sovereign debt and relates it to the evolution of the legal principles underlying the sovereign debt market and the experience of the most recent debt crises and defaults. It finds limited support for theories that explain the feasibility of sovereign debt based on either external sanctions or exclusion from the international capital market and more support for explanations that emphasize domestic costs of default. The paper concludes that there remains a case for establishing institutions that reduce the cost of default but the design of such institutions is not a trivial task.